Green Route Synthesis of Silver Nanoparticles Mediated by Cassia alata Leaf and Zingiber officinale Extracts as Excellent Antibacterial Agents - Mecca Abdia Mtutia Hasan; Akbar Evander Maulana; Ningsih Amilia Puspita; Syabila Oktavia Nur; Laily Tsaniyatur Rizqi Nurul; Nikmah Ainun; Subradra ST. Ulfawanti Intan; Taufiq Ahmad (BIO Web of Conferences)
This research explores the green route synthesis in producing silver nanoparticles (Ag NPs) mediated by Cassia alata leaf and Zingiber officinale extracts using the maceration method as bioreductor agents. Furthermore, this study also investigates the potential antibacterial application of the Ag NPs against bacteria Staphylococcus aureus. The particle size of Ag NPs derived from Cassia alata leaf extract was around 42.5 ± 0.3 nm, smaller than those from Zingiber officinale extract with a value of 44.4 ± 0.6 nm. In addition, Fourier-transform infrared spectroscopy data analysis revealed that the OH, C=O, and CH phenolic groups were involved in reducing Ag+ to Ag0. Meanwhile, the results of antibacterial activity showed that Ag NPs synthesized using Cassia alata leaf extract offered more excellent antibacterial activity than those from the Zingiber officinale extract. The inhibition zone diameter of the Ag NPs synthesized using Cassia alata leaf extract was 14.5 ± 2.2 mm. In comparison, the Ag NPs synthesized from the Zingiber officinale extract had an inhibition zone diameter of 10.5 ± 0.9 mm. Therefore, the results of this work support the development of environmentally friendly nanotechnology-based antibacterial therapy.